AB0693 Patients with chronic inflammatory arthropathies treated with golimumab achieve a higher serum level of drug if used as the first or second biological drug. (15th June 2017) - Rosas, J; Marco-Mingot, M; Senabre-Gallego, JM; Llinares-Tello, F; Pons, A; Barber, X; Santos-Soler, G; Salas, E; Cano, C; Lorente, M; Sanchís-Selfa, M; Molina, J; et al.
Abstract : Objectives: To know the influence of the order of introduction of Golimumab (GLM), on clinical efficacy in ankylosing spondylitis (AS), psoriatic arthritis (PSA) and rheumatoid arthritis (RA). Methods: A prospective, observational study, in 46 consecutive patients with AS, APS and RA, treated with GLM. Data: epidemiological, concomitant DMARD, time of disease evolution, HLA-B27, RF and ACPA; from GLM: order of introduction, time in treatment, serum level and anti-GLM Ab. The clinical response was assessed in AS patients using BASDAI, BASFI, ASDAS-VSG. In patients with RA or peripheral APS, DAS28-VSG, DAS28-PCR and SDAI. Serum levels of GLM and anti-GLM Ab were determined by ELISA (Progenika, Grifols SA, Spain). Serum cutoff levels for serum GLM levels: 36 ng/mL and for anti-GLM Ab: UA>20 AU/mL. Samples were extracted just prior GLM administration (trough level) and stored frozen at -80°C until analysis. Results: Of 33 (72%) AS patients: 52% were males, mean age 53±12 years, mean BMI 28±4, disease mean evolution 16±12 years and in GLM: 1.3±1.1 years, 30% received DMARD, being GLM the first anti-TNF in 25%, second 37%, third 25% and fourth in 13%. The mean GLM level was 0.77±0.62 mg/mL and the prevalence of anti-GLM antibodies was 6%. In the 5 patients with RA and 8 with APS: 23% were men, mean age of 55±11 years, mean BMI 28±6, mean disease evolution of 10.5±8 years and in GLM of 2±1.5 years, the 85% of patients received DMARD, being GLM the first anti-TNF in 31%, second 15%, third 31% and fourth 23%. The mean GLM level was 0.703±0.53 mg/L. No anti-GLM Ab were detected. Conclusions: 1. The overall prevalence of anti-GLM Ab was 6% and 17% in AS patients. Not detecting in patients with RA or PSA. 2. Serum GLM level was higher among the patients receiving it as the 1st or 2nd anti-TNF. 3. In AS GLM as 3rd or 4th anti-TNF were able to achieve clinical remission, similar to that achieved as 1st or 2nd drug. Acknowledgements: The study was supported by a grant from the Fundaciόn Española de Reumatología (FVR/2012) and the Asociaciόn para la Investigaciόn en Reumatología de la Marina Baixa (AIRE-MB). Disclosure of Interest: None declared